Implementation Analysis of the Role of Promotional Media, Husband Support, and the Role of Health Professionals on Visual Inspection Acetate Test at Community Health Centres - Nopitasari, Susi; Lilis Suryani; Ali Harokan (STIKes Al-Ma'arif Baturaja, 2024)
Cancer is still one of the highest causes of death in the world, still not achieving the coverage of IV test examinations in women of childbearing age in the Puskesmas work area, where achievements are still below the achievement of national targets This study aims to determine the factors associated with the implementation of the IVA Test examination at the Kota Baru Health Center, East Ogan Komering Ulu Regency in 2024. This research design is quantitative with a crossectional approach. The population of this study were women of childbearing age (WUS) in 2024. The sample in this study amounted to 84 people. Inclusion criteria for women of childbearing age who are willing to become respondents, while the exclusion criteria are in a state of illness. The sampling method uses Purposive sampling. This study was conducted on 07-29 February 2024. Data collection using questionnaires. Bivariate data analysis using Chi-Square test and multivariate logistic regression. The results showed there was a relationship between knowledge (p value 0.016), husband support (p value 0.000), promotional media (p value 0.000) and the role of health workers (p value 0.015). There is no relationship between age (p value 0.50), age at first marriage (p value 0.42) and attitude (p value 0.18) with the implementation of the VIA test at the Kota Baru Health Centre, East Ogan Komering Ulu Regency in 2024. The most dominant factor with the implementation of VIA examination is husband support (p value 0.000). The conclusion is that there is a relationship between knowledge, husband support, promotional media and the role of health workers with the implementation of the VIA test at the Kota Baru Health Centre, East Ogan Komering Ulu Regency in 2024. Suggestions for the Puskesmas should be in the implementation of the IVA tets method, involve the husband, provide counseling to the family so that the implementation can run well.